tính :
a) \(\sqrt{36}\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(A=2\sqrt{2}+3\sqrt{2}-4\sqrt{2}=\sqrt{2}\)
B=6+18-8=16
\(A=2\sqrt{2}+3\sqrt{2}-4\sqrt{2}=\sqrt{2}\\ B=2\cdot3+3\cdot6-8=6+18-8=16\)
\(3\sqrt{144}-5\sqrt{49}+\dfrac{1}{2}\sqrt{36}\)
\(=3.12-5.7+\dfrac{1}{2}.6\)
\(=36-35+3=4\)
1.
\(A=3log_{2^2}\sqrt{a}-log_{2^{-1}}a^2+2log_{a^{\dfrac{1}{2}}}a\)
\(=3.\dfrac{1}{2}.\dfrac{1}{2}log_2a-\left(-1\right).2.log_2a+2.2.log_2a\)
\(=\dfrac{27}{4}log_2a\)
2.
\(log_{12}36=\dfrac{log_236}{log_212}=\dfrac{log_2\left(3^2.2^2\right)}{log_2\left(3.2^2\right)}=\dfrac{log_23^2+log_22^2}{log_23+log_22^2}\)
\(=\dfrac{2.log_23+2}{log_23+2}=\dfrac{2a+2}{a+2}\)
cho e hỏi tại sao \(3\log_{2^2}\sqrt{a}\) lại bằng \(3.\dfrac{1}{2}.\dfrac{1}{2}\log_2a\) và \(2\log_{a^{\dfrac{1}{2}}}a=2.2.\log_2a\)
Câu 1 :
a, \(=8+4-2.6=12-12=0\)
b, đk : x > 0 ; x khác 1
\(P=\left(\dfrac{\sqrt{x}+1-2\sqrt{x}}{\sqrt{x}\left(\sqrt{x}+1\right)}\right).\dfrac{x+\sqrt{x}}{1-\sqrt{x}}=\dfrac{1-\sqrt{x}}{1-\sqrt{x}}=1\)
\(\sqrt{36}=\sqrt{6^2}=6\)
cảm ơn